A diamond for his defiant Cinderella - Hall, Lorraine, 1982- (Harlequin presents, 2024)
"Find her a husband, or wed her himself? Ultra rich Spaniard Javier Alatorre's life is exactly how he wants it--before he's named guardian of infuriatingly attractive Matilda Willoughby. If she doesn't say 'I do' before she turns twenty-five, he will have to step in as her husband. Matilda loathes Javier's plan to marry her off. He can drag her to galas and introduce her to a dozen millionaires, but she won't accept their diamonds! As she clashes with Javier at every turn, her burning hatred soon turns into scorching need. And Matilda is unprepared for how thin the line between love and hate really is! "--